2021
DOI: 10.2991/assehr.k.211110.200
|View full text |Cite
|
Sign up to set email alerts
|

Development of Junior High School Mathematics E-Modules Based on Project Based Learning Integrated by Merdeka Belajar

Abstract: Ki Hajar Dewantara argues that Merdeka Belajar is the freedom given to student seeking all knowledge by themselves using their minds. Project-based learning will accommodate student independence because it will result in higher student engagement and deep concept understanding. The development of SMP Mathematics E-modules in the form of the latest interactive project-based learning e-modules that are integrated with Merdeka Belajar is very necessary because interactive e-modules can help today's students to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…There were some hindering factors of the teacher's role, they are teachers' lack of ability to develop and apply varied learning methods; lack of teacher knowledge about the students at hand such as students' intelligence levels, talents and interests; teachers are less mature in preparing a set of lessons so that it hinders the implementation of learning; and lack of facilities available to support learning. In student's side, hindering factors for the formation of the Profile Pelajar Pancasila at school such as the attitude of the lazy character of a small number of students, the inhibiting factor of mutation students who are not accustomed to living in discipline, the limitations of teachers in designing good lesson plans, the limitations of teachers in using media, technology and various learning resources, and the lack of time available for teaching and learning activities (Cahyono, 2022;Sagala & Widyastuti, 2022). Another research also found several factors that support and hinder the role of Guru Penggerak at Junior High School Jikumerasa in Maluku province.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were some hindering factors of the teacher's role, they are teachers' lack of ability to develop and apply varied learning methods; lack of teacher knowledge about the students at hand such as students' intelligence levels, talents and interests; teachers are less mature in preparing a set of lessons so that it hinders the implementation of learning; and lack of facilities available to support learning. In student's side, hindering factors for the formation of the Profile Pelajar Pancasila at school such as the attitude of the lazy character of a small number of students, the inhibiting factor of mutation students who are not accustomed to living in discipline, the limitations of teachers in designing good lesson plans, the limitations of teachers in using media, technology and various learning resources, and the lack of time available for teaching and learning activities (Cahyono, 2022;Sagala & Widyastuti, 2022). Another research also found several factors that support and hinder the role of Guru Penggerak at Junior High School Jikumerasa in Maluku province.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these problems, the government implemented a new curriculum, namely the independent curriculum. Merdeka Belajar is an approach that is taken so that students can select the subjects of interest (Handayani et al, 2021;Sagala & Widyastuti, 2022). This is done so that students can optimize their talents and can make the best contribution in working for the nation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a system that is not very good can be very good if all its elements coordinate with each other. Thus, the good and bad of the education system is determined by the coordination of each of its elements (Sagala & Widyastuti, 2021).…”
Section: Introductionmentioning
confidence: 99%